2022
DOI: 10.14738/abr.107.12613
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Prevention Strategies: An Integrative Approach on the Role of Forensic Accounting

Abstract: This study examined the role that forensic accounting play in aiding the success of fraud prevention strategies in combating frauds at both corporate and national levels. The study adopted the exploratory research design methodology involving extensive review of published articles, periodicals and other materials relevant to the subject matter. The study found that while the use and deployment of forensic accounting tools and techniques have made appreciable progress in the developed world, its appreciation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It therefore recommends establishing a dedicated forensic department staffed by qualified personnel at each financial institution. Amahalu, Obian and Ezechukwu (2017) in Olubunmi (2022), in their study, focuses on building a relationship between the use of forensic accounting techniques and fraud detection in selected depository banks. The results showed that the use of financial accounting techniques had a positive impact on the prevention and detection of financial fraud at selected financial institutions.…”
Section: Fokus Ekonomimentioning
confidence: 99%
“…It therefore recommends establishing a dedicated forensic department staffed by qualified personnel at each financial institution. Amahalu, Obian and Ezechukwu (2017) in Olubunmi (2022), in their study, focuses on building a relationship between the use of forensic accounting techniques and fraud detection in selected depository banks. The results showed that the use of financial accounting techniques had a positive impact on the prevention and detection of financial fraud at selected financial institutions.…”
Section: Fokus Ekonomimentioning
confidence: 99%
“…This article thus empirically investigated the role of forensic auditing techniques in responding to the risks of financial statement fraud among selected NGOs in the eThekwini region, focusing on the Durban central business district, (CBD) where many of the most prominent NGOs are located, to test whether or not proactive forensic audit techniques significantly respond to the risks of financial statement fraud among NGOs in the eThekwini region. Ogunode and Dada (2022) investigated the similarities between forensic auditing and forensic accounting. Descriptive and inferential statistics were employed, and ANOVA (Analysis of Variance) was used to analyse the data, compare the level of agreement in the responses to the questionnaire and test the hypotheses.…”
Section: Introductionmentioning
confidence: 99%